(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2020)
Asian soybean rust is an aggressive disease and chemical control must be handled assertively to minimize productivity damage. The objective was to evaluate systemic fungicides and multisite mancozeb, combined or not, and the effects on disease control and soybean yield, cv. ’BMX Lança’. The work was conducted in the field in the 2016/17 and 2017/18 crops, in a randomized complete block design, with four replications. The following treatments were evaluated: T+P) trifloxystrobin + prothioconazole; A+B) azoxystrobin + benzovindiflupyr; T+P+MB) trifloxystrobin + prothioconazole + mancozeb; A+B+MB) azoxystrobin + benzovindiflupyr + mancozeb; MB) mancozeb; and Control (without fungicide application). After the occurrence of the first symptoms of the disease, the severity (%) was evaluated in five trifolia per plot, every seven days, making it possible to calculate the area under the disease progress curve (AUDPC). The yield components and productivity (kg ha-1) were also evaluated. In both crops, the combination of systemic fungicides and mancozeb reduced the severity (%) and progress of Asian rust, reaching a control above 81%. Treatment with trifloxystrobin + prothioconazole + mancozeb (T+P+MB) obtained the highest percentages of control (94.5% - 2016/17, and 93.7% - 2017/18) of Asian rust, and provided, in the 2016/17 crop, productivity at 15 sc ha-1, in relation to the fungicide applied alone (T+P). The combination of systemic fungicides and mancozeb, as proposed in this work, reduces the severity and progress of Asian rust and ensures the maintenance of the productive potential of the soybean.